The Legal Regulation of Overtime Hours under the Saudi Labor Law - Amaal Abdullah Mrzoug Al-saedi; Amal Mohammed Shalabi Khadragey (International Journal of Law Research and Studies, 2025)
The primary objective of this study is to clarify the legal framework governing overtime hours under the Saudi Labor Law. The study adopts the analytical method as the main approach to examine and analyze the relevant provisions of the Saudi Labor Law and its implementing regulations concerning overtime hours. It also reviews judicial precedents to develop a clearer legal understanding of practical related to the subject of the study. Furthermore, the comparative method is employed as needed, by highlighting the differences between the labor laws of Iraq, Jordan, and The United Arab Emirates, and the Saudi Labor Law. The study reached several findings, most notably: the Saudi legislator has placed restrictions on the authority granted to the employer when faced with situations that permit assigning the worker to overtime hours, due to the broad authority employers possess to require employees to work overtime without the necessity of obtaining their consent. The study also concluded with several recommendations, most notably: advising the Saudi legislator to require employers to issue overtime assignments in an official manner, originating from the relevant department within the establishment, whether in written or electronic form. This is to ensure proper documentation of the assignment and facilitate proof in the event of a dispute.